2005
DOI: 10.1002/chem.200500091
|View full text |Cite
|
Sign up to set email alerts
|

Water Superstructures within Organic Arrays; Hydrogen‐Bonded Water Sheets, Chains and Clusters

Abstract: A strategy for encouraging the formation of extended water arrays is presented, in which molecules that contain a 1,4-dihydroquinoxaline-2,3-dione core are used as supramolecular hosts for the accommodation of guest water molecules and arrays. These molecules were selected as they contain a hydrophilic oxalamide-based "terminus" that allows water molecules to hydrogen-bond to the host organic molecules as well as to each other. The host molecules also contain a hydrophobic "end" based upon an aromatic ring, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
39
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(44 citation statements)
references
References 67 publications
5
39
0
Order By: Relevance
“…Metal bonded water molecules are also found and one of these water molecules is disordered with one fluoride ion in a neutral distorted octahedron. It must be noted that pentagons and octagons of water molecules are not encountered in fluoride metalates while they are frequently found in clathrates [15,16], in organic crystals [17] or in ice structures [18].…”
Section: Environment Of H 2 O Moleculesmentioning
confidence: 99%
“…Metal bonded water molecules are also found and one of these water molecules is disordered with one fluoride ion in a neutral distorted octahedron. It must be noted that pentagons and octagons of water molecules are not encountered in fluoride metalates while they are frequently found in clathrates [15,16], in organic crystals [17] or in ice structures [18].…”
Section: Environment Of H 2 O Moleculesmentioning
confidence: 99%
“…The β forms are less stable and transform to the monohydrates at lower temperatures. It is not always true that related compounds crystallise as related hydrates, as shown by Oxtoby et al [54] The authors investigated a set of four closely related 4,4-dihydroquinoxaline-2,3-diones in order to understand water cluster formation, which resulted in the observation of zero-, one-and two-dimensional arrays of water. The authors concluded that in the formation of these hydrated crystal forms not only the strong hydrogen bonds are involved but indeed at number of competing and relatively weak interactions control the formation of specific arrays.…”
Section: Single Crystal X-ray Structures Of Hydratesmentioning
confidence: 99%
“…[15][16][17] Hydrazones (where R = H) can form supramo-lecular arrays in the solid state due to the presence of the protic NH 2 group available for hydrogen bonding, a feature which is being exploited in the crystal engineering field. [18][19][20][21][22][23] The ligands chosen for this study are shown in Figure 2, with the expectation of conveying different steric demands on the titanium(IV) centre and facilitating the formation of different arrays in the solid state. …”
Section: Introductionmentioning
confidence: 99%